Pendampingan Pembuatan E-Learning Dengan Moodle Yang Dipadukan Dengan Software Matematika Geogebra Untuk Guru Matematika di SMP Muhammadiyah Se-Kecamatan Godean, Sleman, Yogyakarta - Syariful Fahmi; Soffi Widyanesti Priwantoro (Universitas Muhammadiyah Surabaya, 2017)
E-learning as one of the benefits of the internet is very supportive for teaching and learning process. Therefore, the mastery ability of e-learning teacher become the key word in e-learning activity in education. The use of computers for the e-learning process using moodle and geogebra in learning mathematics plays an important role as a medium to create effective and efficient learning for teachers in SMP Muhammadiyah 1 Godean, SMP Muhammadiyah 2 Godean, SMP Muhammadiyah 1 Minggir, SMP Muhammadiyah 2 Minggir, SMP Muhammadiyah 1 Mlati. The existence of e-learning will facilitate teachers and students in receiving mathematics lessons and also enhance the quality of teaching and learning. The accompaniment of the implementation of IbM training using e-learning using moodle combined with geogebra was conducted at SMP Muhammadiyah 1 Godean and resulted in e-learning learning media. The mentoring also resulted in an understanding with the principal that the training could be continued for other subjects.